Emerging Technologies and Sustainability in Lagos State Supply Chain Globalization Policy - Oluwaseyi Matthew Adetoba; Ibrahim Korede Hassan; Jacob Fatile; Kabiru Genty (Bina Nusantara University, 2025)
Lagos State, Nigeria's economic hub, has embraced globalization to develop its supply chain infrastructure, aiming to enhance trade and economic growth. However, the rapid emergence of disruptive technologies has raised significant sustainability concerns. The state faces challenges such as infrastructure deficits, the digital divide, trade disruptions, and geopolitical tensions, which complicate its participation in the globalized supply chain while striving for sustainable development. This study assesses Lagos State's supply chain policies through the lens of emerging technologies and sustainability issues. Using qualitative methods, including key informant interviews and content analysis, the research examines how Lagos can leverage new technologies to enhance supply chain sustainability. The findings reveal notable progress in infrastructure development but highlight persistent challenges in balancing global trade participation with sustainable practices. The study concludes that Lagos State's supply chain policy can drive economic growth by harnessing emerging technologies and prioritizing sustainability. Recommendations include increased investment in research and development, regular policy reviews, and strengthened stakeholder collaboration to address sustainability challenges effectively.